2007
DOI: 10.2460/javma.230.11.1653
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of clinical status, renal function, and hematopoietic variables after unilateral nephrectomy in canine kidney donors

Abstract: Renal and hematopoietic variables were within reference ranges in dogs examined up to 2.5 years after unilateral nephrectomy. Compensatory renal hypertrophy was greatest in dogs < 1 year of age at donation. Donor age, along with histocompatability, may be an important factor in selecting dogs for kidney donation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 16 publications
0
17
0
Order By: Relevance
“…Removal of a kidney, a part of the liver, a salivary gland or a plaintive gland causes an increase in the proliferative activity of the remaining organ or gland (13)(14)(15)(16)(17)(18)(19)(20). A factor appears in blood serum which enhances cell proliferation as early as 12 h after small bowel resection (21).…”
Section: Discussionmentioning
confidence: 99%
“…Removal of a kidney, a part of the liver, a salivary gland or a plaintive gland causes an increase in the proliferative activity of the remaining organ or gland (13)(14)(15)(16)(17)(18)(19)(20). A factor appears in blood serum which enhances cell proliferation as early as 12 h after small bowel resection (21).…”
Section: Discussionmentioning
confidence: 99%
“…Removal of a kidney, a part of the liver, a salivary gland or a plaintive gland causes an increase in the proliferative activity of the remaining organ or gland ( Urie et al, 2007 ;Haxhija et al, 2007;Martin et al, 2008;Juno et al, 2002;Nelson et al, 2002;Vlastos et al, 2008;Aussilhou et al, 2008;Wilms et al, 2008). A factor appears in blood serum which enhances cell proliferation as early as 12 h after small bowel resection (Juno et al, 2003.).…”
Section: (Patho)physiological Processes Of Quantitative Organ (Tissuementioning
confidence: 99%
“…For both humans [7][8][9][10][11] and veterinary [13][14][15] patients, these complications include stent migration, 7-10,13 encrustation, 7,10,13 ureteral tissue reaction, 13,15 hematuria, 10 recurrent urinary tract infection, 10,13 ureterovesicular reflux, 10,13 and dysuria. 2,[16][17][18] Ureteronephrectomy should be avoided whenever possible, given that the underlying etiology of the condition is an obstructed ureter rather than a diseased kidney, the concurrent pyelonephritis is likely affecting the renal function of both kidneys, and these patients are prone to urolithiasis that could develop a contralateral ureteral obstruction. 10,13 Information on the treatment of pyonephrosis in the veterinary literature is sparse.…”
mentioning
confidence: 99%
“…7,12,13,15 In human patients, the decision of which technique to use is based on clinician preference, patient stability, anatomy, coagulation status, underlying cause of obstruction, expertise of the treatment team, and available equipment. 3,8,13 Two studies 17,18 found that nephrectomized patients had high creatinine concentration following surgery. Previously described treatments include ureteronephrectomy, nephropyelotomy, or ureterotomy.…”
mentioning
confidence: 99%
See 1 more Smart Citation